A szabadalmak szerepe az innovatív startupok esetén - Lányi, Beatrix (Közép-Európai Közlemények, 2016)
Innovation belongs to one of the main sources of competitive advantage but not all invention results in patent. Researches have proved the patents have effect on the valuation of companies. It is especially true in case of start-ups. Start-upsare innovative and they are characterised by extremely high growth potential as well as risk-taking ability. They are globally scalable and are continuously searching for the right business model. Start-ups can be successful on the market if they offer new advantages to their clients or totally renew their business offering. If they are able to utilise their innovative ideas in the right way it can lead to the enhancement of value creation. An effective way of protecting innovative ideas is patenting. Patent can be considered as an indicator of quality. One of the main advantages of patenting for start-ups is that it ensures security for investors and contributes to more value-added to the image of the company. All this suggest that patents can be used for information and reliability guarantee purposes. Patents are not prevailingly used by Hungarian start-ups nevertheless it implies significant advantages.